Implementation of an integrated leaflet and video education program (LEAVIN): A quality improvement initiative in perioperative nursing - Hafid Hafid; Ridlwan Kamaluddin; Murdiyana Ahmad (Indonesian Nursing Journal, 2026)
Background: Preoperative anxiety affects a substantial proportion of surgical patients and may compromise psychological readiness and physiological stability before anaesthesia. Pre-anaesthesia counselling at a Regional Public Hospital in East Jakarta was previously delivered verbally without structured visual or audiovisual educational media. Purpose: This study describes the development of an integrated leaflet and video pre-anaesthesia education (LEAVIN), accessible via a quick-response (QR) code, and reports the preliminary effect of its implementation on preoperative anxiety. Method: This was a quality-improvement initiative using a one-group pre-test–post-test design without a comparison group, conducted at the preoperative preparation unit of a Regional Public Hospital in East Jakarta, from February to April 2026. A needs assessment using items adapted from the Amsterdam Preoperative Anxiety and Information Scale (APAIS) was conducted among 21 patients. Educational content on anaesthesia procedures, pre-anaesthesia preparation, possible side effects, and a deep-breathing relaxation technique was developed, validated by an anaesthesiologist and peer nurses, and packaged as a leaflet and a QR-code-linked video. The intervention was delivered to 12 patients, whose anxiety was assessed before and after education using the Numeric Rating Scale for Anxiety (NRS-A). Result: At baseline, 52.4% of patients feared anaesthesia, 61.9% reported persistent worry about anaesthesia, and 52.4% wanted more information. Following LEAVIN education, anxiety decreased in 7 of 12 patients (58.3%), while 5 patients (41.7%) reported no change. Conclusion: Integrated leaflet and video education was feasible within routine perioperative nursing care and was associated with reduced preoperative anxiety in most evaluated patients. Larger controlled studies with validated instruments are needed to confirm its effectiveness.